2021
DOI: 10.3389/fpsyg.2021.725146
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Reliability of Parental Reports and Direct Screening of Developmental Outcomes in Toddlers at Risk

Abstract: Developmental screening is a practice that directly benefits vulnerable and low-income families and children when it is regular and frequently applied. A developmental screening tool administered by parents called CARE is tested. CARE contains a compilation of activities to report and enhance development at home. Hundred and fifty-seven families in Bogotá (Colombia) initially responded to a call to participate in developmental screening tools’ validation and reliability study. All children (Average: 42.7 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(133 reference statements)
0
1
0
1
Order By: Relevance
“…El DDST es el instrumento de observación de mayor utilización y validación en múltiples y recientes estudios (McCoy, et al, 2018). Un primer piloto en el uso de CARE (Giraldo & Schafer, 2021), indica óptimas propiedades diagnósticas para el monitoreo infantil (Sensibilidad = .95, Especificidad =.85, LR+ =6.17, LR-= .06). Sin embargo, hasta el momento no se ha diseñado una intervención que además de entregar la cartilla CARE permita acompañar el monitoreo parental.…”
Section: Introductionunclassified
“…El DDST es el instrumento de observación de mayor utilización y validación en múltiples y recientes estudios (McCoy, et al, 2018). Un primer piloto en el uso de CARE (Giraldo & Schafer, 2021), indica óptimas propiedades diagnósticas para el monitoreo infantil (Sensibilidad = .95, Especificidad =.85, LR+ =6.17, LR-= .06). Sin embargo, hasta el momento no se ha diseñado una intervención que además de entregar la cartilla CARE permita acompañar el monitoreo parental.…”
Section: Introductionunclassified
“…Results of a receiver operating curve (ROC) analysis indicated that parental report using CARE is a satisfactory tool for screening diagnostics (Area Under the Curve—AUC: 0.894, trapezoidal Wilcoxon area). All the reliability, agreement and diagnostic-characteristics analysis results were previously carried and published before the intervention and efficacy study [ 38 ]. However, it is important to note that using CARE solely as a developmental screening tool, without incorporating its intended characteristics as a parental intervention, does not constitute an actual intervention.…”
Section: Introductionmentioning
confidence: 99%